Employee Testing, Tracing, and Disclosure as a Response to the Coronavirus Pandemic - Matthew T. Bodie; Michael McMahon (Washington University Journal of Law & Policy, 2021)
Testing, tracing, and disclosure is a common workplace safety measure implemented to mitigate the spread of the coronavirus in the United States. The absence of a coordinated national response presented local governments and private businesses with difficult questions regarding operation in the pandemic. This Article analyzes the legal framework for this approach, specifically addressing concerns of invasion into worker privacy. This Article encourages employers to develop their own testing, tracing, and disclosure systems to prevent widespread workplace outbreaks, avoid costly litigation, and preserve their business operations. Steps integral to the system include: providing clear notice to employees about what is required of them and how the employer will use employees’ personal information; limiting sharing of personal information to those who “need to know;” crafting disclosures that protect individual privacy while promptly alerting affected employees of potential virus exposure; and maintaining strong data security systems and practices.
Keywords: COVID; COVID-19; coronavirus; coronavirus pandemic; pandemic; employment; employee rights; worker privacy; privacy; personal information; worker; workers; testing; tracing; disclosure